2019
DOI: 10.1186/s12864-019-5967-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of human T cells following a single stimulation of peripheral blood mononuclear cells with anti-CD3 antibodies

Abstract: Background Anti-CD3 immunotherapy was initially approved for clinical use for renal transplantation rejection prevention. Subsequently, new generations of anti-CD3 antibodies have entered clinical trials for a broader spectrum of therapeutic applications, including cancer and autoimmune diseases. Despite their extensive use, little is known about the exact mechanism of these molecules, except that they are able to activate T cells, inducing an overall immunoregulatory and tolerogenic behavior. To … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
2
6
1
Order By: Relevance
“…The most altered pathways were associated with cell proliferation and immune response in stimulated compared to unstimulated cells. A previous RNAseq analysis of PBMC cultures stimulated with anti-CD3 antibodies also showed increased expression of pathways involved in immune function and cell division [51], although differences between this previous report and the present findings may be due to analysis of a mixture of cell types in the previous study. Both FO and tCSO increased the number of up-regulated transcripts in pathways involved in cell division [52] and immune-regulatory pathways such as interleukin-17 and interleukin-10 signalling [20,53].…”
Section: Discussioncontrasting
confidence: 89%
“…The most altered pathways were associated with cell proliferation and immune response in stimulated compared to unstimulated cells. A previous RNAseq analysis of PBMC cultures stimulated with anti-CD3 antibodies also showed increased expression of pathways involved in immune function and cell division [51], although differences between this previous report and the present findings may be due to analysis of a mixture of cell types in the previous study. Both FO and tCSO increased the number of up-regulated transcripts in pathways involved in cell division [52] and immune-regulatory pathways such as interleukin-17 and interleukin-10 signalling [20,53].…”
Section: Discussioncontrasting
confidence: 89%
“… 39 In addition, the activation of T cells by anti-CD3 antibodies results in increased expression of various cytokines, including IFNy. 30 As shown in this study, DES1 and ShK are potent inhibitors of all three outcomes, as expected based on ~1000-fold differences in potencies against Kv1.3 obtained from patch clamp measurements. DES1 required ~10x–100x higher concentrations than ShK to elicit its ex vivo efficacy [IC50 values of ~100 nM vs ~50–500 pM for DES1 and ShK, respectively, against Kv1.3 obtained from electrophysiology with the channel expressed in mammalian cells].…”
Section: Discussionsupporting
confidence: 85%
“…DES1 inhibited the expression of these surface markers in a concentration-dependent manner, and the inhibition reached significance at 1000 nM [CD25+: p = 0.001; CD69+: p = 0.0005]. As T-cell activation by anti-CD3 antibodies results in cytokine release, 30 supernatants were additionally analysed by Luminex assays for IFNy, IL-4, and IL-10 levels. As shown in Figure 2C , anti-CD3 significantly increased the secretion of cytokines [IFNy: p = 0.0006; IL-4: p = 0.002; IL-10 p = 2 E-05].…”
Section: Resultsmentioning
confidence: 99%
“…scRNAseq of T cells from the clinical trials of teplizumab and other immunotherapies in T1D could offer an amazing opportunity to identify all biomarkers predictive of successful treatment. For example, scRNAseq studies have shown a variety of phenotypic markers induced in vitro with anti-CD3 antibodies in human PBMC, including a variety of interleukin receptors and markers of regulation and exhaustion including FOXP3, CTLA4, TNFRSF18, LAG3 and PDCD1 (102). In contrast, anti-CD3/ CD28 stimulation of PBMC analysed with scRNAseq and CITEseq, showed phenotypes strongly associated with activation (although memory subsets also upregulated senescence) (103).…”
Section: Biomarkers In Clinical Trialsmentioning
confidence: 99%